Robust Object Tracking Algorithm using Harris Detector based Bayesian Filters - Rajiv Kapoor, Neetu Gupta, MunishVashishath (International Journal of Advanced Science and Technology, 2020)
Computer vision systems represent an essential tool for a broad range of video surveillance applications. Two of the most noteworthy challenges for these systems are Object tracking and anomalous activity detection. Numerous algorithms were developed for the purpose of tracking, e.g In this research work the objective of object tracking for anomaly detection has been achieved by making use of filters. The filters that have been used for tracking and anomaly detection are the Bayes Filters. They work on the concept of prediction. The idea is to get samples of the posterior distribution from the hidden states .This paper presents the Particle filter combined with the Harris feature descriptor for tracking moving objects in a video